PERAN KANTOR WILAYAH KEMENTERIAN HUKUM DAN HAM DALAM KEWENANGAN EXECUTIVE PREVIEW PERATURAN DAERAH DAN PERATURAN KEPALA DAERAH - Prabowo, Raffel Pradityo; Ummul Firdaus, Sunny (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2024)
This research focuses on the executive preview authority carried out by the Regional Office of the Ministry of Law and Human Rights (Kanwil Kemenkumham) in the process of forming Regional Regulations (Perda/Perkada). The objectives of this study are, firstly, to understand the implementation of the executive preview authority in Perda/Perkada. Secondly, to identify the obstacles encountered in its implementation process. The research method employed is empirical legal research, using the Sociology of Law approach and qualitative in nature. Legal materials were collected by conducting field research at the Kanwil Kemenkumham Central Java and studying literature analyzed qualitatively. The results of this study indicate that: Firstly, the implementation of the executive preview authority conducted at the Kanwil Kemenkumham Central Java goes through these stages: submission of harmonization requests, administrative examination, conceptual analysis, harmonization meeting, preparation of harmonization minutes, approval endorsement, submission of harmonization completion letters. However, this process has not been ideally executed as not all regions conduct executive previews despite the Legal Regulations stating it is mandatory, yet there are no sanctions when regions fail to follow the process. Secondly, obstacles found in the implementation of the executive preview include the lack of Human Resources in Regulation Drafting, the weakness of executive preview authority in legal regulations, and the lack of regional understanding of the administrative document requirements that should be fulfilled before submitting harmonization requests.